KONSEP INTEGRATION LAYER DALAM PEMBANGUNAN DATA WAREHOUSE - I WAYAN PULANTARA; I WAYAN SANTIYASA (Mathematics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2007)
Information availability in exact time is one of keys for correct decision making. One of thesolutions is by developing a Data Warehouse for supporting decision making. In general DataWarehouse contains Dependent Data Mart (DDM), Integration Layer(IL), and Extract-Transform-Load (ETL). Integration Layer is a database that contains data that already integrated,stored in aid for one or more decision support system. For its data source, integration layerrequire Extract-Transform-Load (ETL) as supplier for clean and integrated data. IntegrationLayer volume would be much larger than any on dependent data mart that its support, so thefocus aspect in developing Integration Layer as core part of Data Warehouse is how to handle ahuge amount of data in considerable performance. Beside that, interfacing aspect is alsoimportant, e.g. how Integration Layer interact with ETL Process and supporting dependent data.